First record of the pencil cardinal Epigonus denticulatus (Perciformes: Epigonidae) in the Azores archipelago. Issue 1 (20th February 2021) - Catarino, Diana; Stefanni, Sergio; Porteiro, Filipe M.; Rosa, Alexandra; Giacomello, Eva
Abstract: The pencil cardinal Epigonus denticulatus is a small deep‐water fish inhabiting continental slopes usually between 300 and 600 m depth. We report the first record of E. denticulatus in the Azores archipelago, where one specimen was found floating by fisherman off Faial island. Meristic and morphometric characters are in accordance with those reported for the species and molecular analyses further supported species identity. The record of E. denticulatus as a native species in the Azores increases the number of Epigonus species in the region to a total of three.